Th1 and Th2 Immune Response in Chronic Hepatitis B Patients during a Long-Term Treatment with Adefovir Dipivoxil - Yanfang Jiang; Zhenhua Ma; Guijie Xin; Hongqing Yan; Wanyu Li; Huining Xu; Chunhai Hao; Junqi Niu; Pingwei Zhao (Mediators of Inflammation)
Adefovir dipivoxil treatment has significantly improved the outcome of chronic hepatitis B virus (HBV) infection. However, it remains largely unknown how immune system responds to the treatment. Chronic HBV patients were treated with adefovir dipivoxil and examined for serum HBV DNA loads, cytokines, and T helper (Th1) and 2 (Th2) cytokine producing T cells during 104 weeks of the treatment. Th1/Th2 cytokines producing T cells were significantly lower in chronic HBV patients as compared to normal individuals. Adefovir dipivoxil treatment led to the increase of Th1/Th2 cytokines producing T cells and serum cytokine levels in association with the decline of HVB DNA load. In contrast, Th1/Th2 cytokines producing T cells remained lower in one patient detected with adefovir dipivoxil resistant HBV A181T/V mutation. This study has established inverse correlation of the increase of Th1/Th2 immunity and the decline of HBV DNA load in chronic HBV patients during adefovir dipivoxil treatment.